The Primary Physis - Brian, James M.; Choi, David H.; Moore, Michael M. (Seminars in Musculoskeletal Radiology, 2018)
The primary physis is responsible for long bone growth in children and adolescents. Injury and physiologic or metabolic stress to the primary physis present unique radiologic findings that are important for radiologists to recognize and diagnose. Appreciation of the anatomy and histology of the primary physis forms the basis for understanding the imaging findings associated with pathologic conditions affecting the primary physis. Salter-Harris injuries, physeal bars, growth arrest lines, rickets, and focal periphyseal edema zones are common conditions with recognizable radiologic presentations. Proper diagnosis of these primary physeal conditions will aid in the treatment of affected pediatric patients.
Keywords: primary physis; Salter-Harris fractures; rickets; physeal bars